IMPLEMENTATION OF SMART IRRIGATION SYSTEM ON CARROT PLANTATION USING INTERNET OF THINGS - Perangin-Angin, Despaleri; -, Yoga Tri Nugraha; -, Evta Indra; Turnip, Mardi; Situmorang, Andreas; Sitompul, Daniel Ryan Hamonangan; -, Ruben (Jurnal Sistem Informasi dan Ilmu Komputer, 2022)
Agriculture is one of the main sectors in Karo Regency, North Sumatra. One of the commodities produced by farmers in Karo Regency is carrot. The inability of farmers to control soil moisture may cause crop damage to a lack of productivity. This research aims to create a monitoring & control system that is integrated with the website to make it easier for farmers to prevent problems that occur. The method used in the research is the design, installation, monitoring, and deactivation. The results obtained from this research are that farmers can now monitor the field conditions in real-time using a web-based monitoring & control system.